Comprehension demands modulate re-reading, but not first-pass reading behavior. Issue 1 (January 2018) - Weiss, Anna Fiona; Kretzschmar, Franziska; Schlesewsky, Matthias; Bornkessel-Schlesewsky, Ina; Staub, Adrian
Several studies have examined effects of explicit task demands on eye movements in reading. However, there is relatively little prior research investigating the influence of implicit processing demands. In this study, processing demands were manipulated by means of a between-subject manipulation of comprehension question difficulty. Consistent with previous results from Wotschack and Kliegl, the question difficulty manipulation influenced the probability of regressing from late in sentences and re-reading earlier regions; readers who expected difficult comprehension questions were more likely to re-read. However, this manipulation had no reliable influence on eye movements during first-pass reading of earlier sentence regions. Moreover, for the subset of sentences that contained a plausibility manipulation, the disruption induced by implausibility was not modulated by the question manipulation. We interpret these results as suggesting that comprehension demands influence reading behavior primarily by modulating a criterion for comprehension that readers apply after completing first-pass processing.